2013
DOI: 10.1111/pre.12015
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐ and digalactosyldiacylglycerol composition of the marennine‐producing diatom, Haslea ostrearia: Comparison to a selection of pennate and centric diatoms

Abstract: Summary Diatoms are one of the largest groups of primary producers in the oceans, yet despite their environmental importance little is known about their plastidial lipid biochemistry. It has been previously reported that Skeletonema species contain primarily C16/C16 and C20/C16 forms of mono‐ and digalactosyldiacylglycerol (MGDG and DGDG, respectively). Likewise, it was also reported that Phaeodactylum tricornutum contains primarily C16/C16 and C20/C20 forms of MGDG and DGDG. We seek to relate their studies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Besides the C20/C16 forms of MGDG, MGDG molecules with C16 FAs at both the sn-1 and sn-2 position can be observed. DGDG exhibits a comparable FA composition to MGDG and is also enriched in EPA (Yongmanitchai and Ward, 1993;Yan et al, 2011;Dodson et al, 2013Dodson et al, , 2014. Like in the MGDG molecule EPA usually occupies the sn-1 position of DGDG while at the sn-2 position C16 FAs are observed.…”
Section: Fatty Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the C20/C16 forms of MGDG, MGDG molecules with C16 FAs at both the sn-1 and sn-2 position can be observed. DGDG exhibits a comparable FA composition to MGDG and is also enriched in EPA (Yongmanitchai and Ward, 1993;Yan et al, 2011;Dodson et al, 2013Dodson et al, , 2014. Like in the MGDG molecule EPA usually occupies the sn-1 position of DGDG while at the sn-2 position C16 FAs are observed.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…As it has been demonstrated for MGDG, DGDG forms with C16 FAs at both the sn-1 and sn-2 positions can be found and DGDG with C20:5 and C16:3 seems to represent the most abundant diatom DGDG molecule. Earlier studies have reported that a difference exists in the FA composition of centric and pennate diatoms and that in the pennate diatoms EPA is replaced by C18 FAs in the MGDG and DGDG molecules (Dodson et al, 2013). However, more recent studies have indicated that the differences in the FA composition of MGDG and DGDG of centric and pennate diatoms may be related to differences in their reaction to environmental temperatures and that EPA is present at lower temperatures and may be replaced by C18 FAs at higher temperatures (Dodson et al, 2014).…”
Section: Fatty Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also relevant to a study in diatoms where MGDG and DGDG molecular species were compared in two centric species (Skeletonema marinoi, Thalassiosira weissflogii) with pinnate species (Phaeodactylum tricornutum, Haslen ostrearia, Navicula perminuta) [22].…”
Section: Lipids In Algaementioning
confidence: 99%
“…Hence galactolipids synthesized according to the “eukaryotic” pathway contain predominantly 18-C fatty acid in both sn –1 and sn –2 positions [ 52 ]. Mono- and digalactosyldiacylglycerols from diatoms are mainly synthesised in the “prokaryotic” pathway, as these compounds contain 16-C fatty acids in the sn–2 position [ 53 , 54 ]. Thus, we can deduce the fatty acid chain length in galactolipids presented in this report.…”
Section: Discussionmentioning
confidence: 99%